Impact of Telehealth Interventions on Medication Adherence for Patients With Type 2 Diabetes, Hypertension, and/or Dyslipidemia: A Systematic Review. Issue 5 (May 2021) - Bingham, Jennifer M.; Black, Melissa; Anderson, Elizabeth J.; Li, Yawen; Toselli, Natalie; Fox, Shawna; Martin, Jennifer R.; Axon, David R.; Silva-Almodóvar, Armando
Objective: To describe telehealth interventions and determine their effect on medication adherence for patients with type 2 diabetes, hypertension, and/or dyslipidemia. Data Sources: PubMed/MEDLINE, EMBASE, Cochrane, CINAHL Plus, PsycINFO, Academic Search Ultimate, International Pharmaceutical Abstracts, Scopus, Web of Science, WHO Global Index Medicus, association websites, and gray literature were searched from January 1, 1998, to December 31, 2019. Study Selection and Data Extraction: Eligible studies reported eHealth, mobile health, and telehealth interventions for adult patients prescribed medications for chronic condition management (eg, type 2 diabetes, hypertension, and/or dyslipidemia). Studies were required to evaluate medication adherence outcomes (eg, medication possession ratio [MPR], proportion of days covered (PDC)]. Randomized controlled trials, cohort studies, and controlled before-and-after studies were included. Multiple reviewers independently extracted data and evaluated risk of bias. Data Synthesis: Of 8693 studies identified, 13 reported either an MPR or PDC and were included in the systematic review. The systematic review demonstrated that electronic health (eHealth) and telehealth interventions were successful at improving medication adherence, whereas mobile health interventions did not improve medication adherence. Relevance to Patient Care and Clinical Practice: This systematic review highlighted the available research and findings of studies assessing interventions to improve medication nonadherence among patients with type 2 diabetes, hypertension, and/or dyslipidemia. The evaluated findings lend support to the need for targeted medication adherence interventions based on patient population and practice settings. Conclusions: Telehealth modalities include telephonic outreach and specialized tools designed to increase health literacy. eHealth and telehealth medication adherence interventions were associated with improved MPR and/or PDC rates.